ANALISIS WACANA PEMBERITAAN PENCALONAN JOKOWI SEBAGAI CALON PRESIDEN 2014 PADA SURAT KABAR HARIAN KOMPAS - Nurcahyo, Dino (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2015)
Mass Media has an important role, not only as a public information source, also as a social control, but also a tool of forming public opinion as well. The news that reported by mass media cover all aspects of peopleâs lives, for examples politics and laws. The author also highlights the news about the candidacy of Joko Widodo as a Presidental candidate in 2014. The purpose of this research is to find the construction reality of news in Kompas Daily Newspaper about the candidacy of Joko Widodo as candidate for president 2014. The framework of thought this research emphasized the mass communication studies with speciffically describe the news in newspaper, related to the social construction reality with the approach of a discourse analysis by Teun A Van Dijk. In this research, the researcher uses a discourse analysis, by using an approach of discourse analysis by Teun A. Van Dijk. Which includes three elements, text, social cognition, and social context. Then, the element of texts divided into three kinds, they are: macro-structure, superstructure, microstructure. All of these elements are considered by author as the right tools to analyze the news about the candidacy of Joko Widodo as presi-dental candidate in 2014 on Kompas daily newspaper. The result of this research is that the whole process of the text, social cognition, and a social context, that the Kompas daily newspaper which tagline is âthe Command of Peopleâs Heartâ is stating Jokowi to be the next President-to-be through their news and contents, it indirectly will affect public opinion to vote for Jokowi.